LEADERSHIP ROLE TO IMPROVE EMPLOYEE PERFORMANCE - Choirul Anwar Al; Istiatin Istiatin; Sudarwati Sudarwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The Global Pandemic by COVID 19 is a challenge for all agencies in the aspect of life, demanding that people innovate and self-management to remain in existence in the development of the industrial world. Good management and human resources are crucial factors in developing a company or organization to achieve the goals that have been set good leadership of the leaders and discipline owned, realized and carried out responsibly from all parties become factors that can improve the performance of employees who impact the agency. This research was conducted at Al Abidin Surakarta Foundation with 42 employees consisting of administrative employees, security and cleaning services. The sample numbered 20 employees, taken by census method. Data analysis tools use multiple linear regression analysis. The results showed leadership and discipline had a positive and significant effect on the performance of employees at Yayasan Al Abidin Surakarta. Leaders who provide transparency, attention, reward, and can put their employees to impact comfort and optimization of performance. Employee discipline in attendance, return, appearance and adherence to regulations influences improving performance at Yayasan Al Abidin Surakarta. Keywords: Leadership Role, Employee Performance,